Nonlinear Imaging of Nanoscale Topological Corner States - Kruk, Sergey S.; Gao, Wenlong; Choi, Duk-Yong; Zentgraf, Thomas; Zhang, Shuang; Kivshar, Yuri (Nano Letters)
Topological states of light represent counterintuitive optical modes localized at boundaries of finite-size optical structures that originate from the properties of the bulk. Being defined by bulk properties, such boundary states are insensitive to certain types of perturbations, thus naturally enhancing robustness of photonic circuitries. Conventionally, the N-dimensional bulk modes correspond to (N – 1)-dimensional boundary states. The higher-order bulk-boundary correspondence relates N-dimensional bulk to boundary states with dimensionality reduced by more than 1. A special interest lies in miniaturization of such higher-order topological states to the nanoscale. Here, we realize nanoscale topological corner states in metasurfaces with C6-symmetric honeycomb lattices. We directly observe nanoscale topology-empowered edge and corner localizations of light and enhancement of light–matter interactions via a nonlinear imaging technique. Control of light at the nanoscale empowered by topology may facilitate miniaturization and on-chip integration of classical and quantum photonic devices.

Nonlinear metasurface combining telecom-range intersubband transitions in GaN/AlN quantum wells with resonant plasmonic antenna arrays - Mundry, Jan; Spreyer, Florian; Jmerik, Valentin; Ivanov, Sergey; Zentgraf, Thomas; Betz, Markus (Optical Materials Express)
We realize and investigate a nonlinear metasurface taking advantage of intersubband transitions in ultranarrow GaN/AlN multi-quantum well heterostructures. Owing to huge band offsets, the structures offer resonant transitions in the telecom window around 1.55 µm. These heterostructures are functionalized with an array of plasmonic antennas featuring cross-polarized resonances at these near-infrared wavelengths and their second harmonic. This kind of nonlinear metasurface allows for substantial second-harmonic generation at normal incidence which is completely absent for an antenna array without the multi-quantum well structure underneath. While the second harmonic is originally radiated only into the plane of the quantum wells, a proper geometrical arrangement of the plasmonic elements permits the redirection of the second-harmonic light to free-space radiation, which is emitted perpendicular to the surface.

Recent progress on metasurfaces: applications and fabrication - Yoon, Gwanho; Tanaka, Takuo; Zentgraf, Thomas; Rho, Junsuk (Journal of Physics D: Applied Physics)

Dielectric travelling wave antennas for directional light emission - Leuteritz, T.; Farheen, H.; Qiao, S.; Spreyer, F.; Schlickriede, Christian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Linden, S. (Optics Express)
We present a combined experimental and numerical study of the far-field emission properties of optical travelling wave antennas made from low-loss dielectric materials. The antennas considered here are composed of two simple building blocks, a director and a reflector, deposited on a glass substrate. Colloidal quantum dots placed in the feed gap between the two elements serve as internal light source. The emission profile of the antenna is mainly formed by the director while the reflector suppresses backward emission. Systematic studies of the director dimensions as well as variation of antenna material show that the effective refractive index of the director primarily governs the far-field emission pattern. Below cut off, i.e., if the director’s effective refractive index is smaller than the refractive index of the substrate, the main lobe results from leaky wave emission along the director. In contrast, if the director supports a guided mode, the emission predominately originates from the end facet of the director.
Keywords: tet_topic_opticalantenna

Observing 0D subwavelength-localized modes at ~100 THz protected by weak topology - Lu, Jinlong; Wirth, Konstantin G.; Gao, Wenlong; Heßler, Andreas; Sain, Basudeb; Taubner, Thomas; Zentgraf, Thomas (Science Advances)
Topological photonic crystals (TPhCs) provide robust manipulation of light with built-in immunity to fabrication tolerances and disorder. Recently, it was shown that TPhCs based on weak topology with a dislocation inherit this robustness and further host topologically protected lower-dimensional localized modes. However, TPhCs with weak topology at optical frequencies have not been demonstrated so far. Here, we use scattering-type scanning near-field optical microscopy to verify mid-bandgap zero-dimensional light localization close to 100 THz in a TPhC with nontrivial Zak phase and an edge dislocation. We show that because of the weak topology, differently extended dislocation centers induce similarly strong light localization. The experimental results are supported by full-field simulations. Along with the underlying fundamental physics, our results lay a foundation for the application of TPhCs based on weak topology in active topological nanophotonics, and nonlinear and quantum optic integrated devices because of their strong and robust light localization.

A wavelength and polarization selective photon sieve for holographic applications - Frese, Daniel; Sain, Basudeb; Zhou, Hongqiang; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nanophotonics)
Optical metasurfaces are perfect candidates for the phase and amplitude modulation of light, featuring an excellent basis for holographic applications. In this work, we present a dual amplitude holographic scheme based on the photon sieve principle, which is then combined with a phase hologram by utilizing the Pancharatnam–Berry phase. We demonstrate that two types of apertures, rectangular and square shapes in a gold film filled with silicon nanoantennas are sufficient to create two amplitude holograms at two different wavelengths in the visible, multiplexed with an additional phase-only hologram. The nanoantennas are tailored to adjust the spectral transmittance of the apertures, enabling the wavelength sensitivity. The phase-only hologram is implemented by utilizing the anisotropic rectangular structure. Interestingly, such three holograms have quantitative mathematical correlations with each other. Thus, the flexibility of polarization and wavelength channels can be utilized with custom-tailored features to achieve such amplitude and phase holography simultaneously without sacrificing any space-bandwidth product. The present scheme has the potential to store different pieces of information which can be displayed separately by switching the wavelength or the polarization state of the reading light beam.

Extremely low-energy ARPES of quantum well states in cubic-GaN/AlN and GaAs/AlGaAs heterostructures - Hajlaoui, Mahdi; Ponzoni, Stefano; Deppe, Michael; Henksmeier, Tobias; As, Donat Josef; Reuter, Dirk; Zentgraf, Thomas; Springholz, Gunther; Schneider, Claus Michael; Cramm, Stefan; Cinchetti, Mirko (Scientific Reports)
Abstract Quantum well (QW) heterostructures have been extensively used for the realization of a wide range of optical and electronic devices. Exploiting their potential for further improvement and development requires a fundamental understanding of their electronic structure. So far, the most commonly used experimental techniques for this purpose have been all-optical spectroscopy methods that, however, are generally averaging in momentum space. Additional information can be gained by angle-resolved photoelectron spectroscopy (ARPES), which measures the electronic structure with momentum resolution. Here we report on the use of extremely low-energy ARPES (photon energy ~ 7 eV) to increase depth sensitivity and access buried QW states, located at 3 nm and 6 nm below the surface of cubic-GaN/AlN and GaAs/AlGaAs heterostructures, respectively. We find that the QW states in cubic-GaN/AlN can indeed be observed, but not their energy dispersion, because of the high surface roughness. The GaAs/AlGaAs QW states, on the other hand, are buried too deep to be detected by extremely low-energy ARPES. Since the sample surface is much flatter, the ARPES spectra of the GaAs/AlGaAs show distinct features in momentum space, which can be reconducted to the band structure of the topmost surface layer of the QW structure. Our results provide important information about the samples’ properties required to perform extremely low-energy ARPES experiments on electronic states buried in semiconductor heterostructures.

All-dielectric silicon metalens for two-dimensional particle manipulation in optical tweezers - Chantakit, Teanchai; Schlickriede, Christian; Sain, Basudeb; Meyer, Fabian; Weiss, Thomas; Chattham, Nattaporn; Zentgraf, Thomas (Photonics Research)

A dielectric metasurface optical chip for the generation of cold atoms - Zhu, Lingxiao; Liu, Xuan; Sain, Basudeb; Wang, Mengyao; Schlickriede, Christian; Tang, Yutao; Deng, Junhong; Li, Kingfai; Yang, Jun; Holynski, Michael; Zhang, Shuang; Zentgraf, Thomas; et al. (Science Advances)
Compact and robust cold atom sources are increasingly important for quantum research, especially for transferring cutting-edge quantum science into practical applications. In this study, we report on a novel scheme that uses a metasurface optical chip to replace the conventional bulky optical elements used to produce a cold atomic ensemble with a single incident laser beam, which is split by the metasurface into multiple beams of the desired polarization states. Atom numbers ~10 7 and temperatures (about 35 μK) of relevance to quantum sensing are achieved in a compact and robust fashion. Our work highlights the substantial progress toward fully integrated cold atom quantum devices by exploiting metasurface optical chips, which may have great potential in quantum sensing, quantum computing, and other areas.

Plasmonic metasurfaces for controlling harmonic generations - Zentgraf, Thomas; Chen, Shumei; Li, Guixin; Zhang, Shuang (Nanoantennas and Plasmonics: Modelling, design and fabrication)

Metasurfaces help lasers to mode-lock - Sain, Basudeb; Zentgraf, Thomas (Light: Science & Applications)

Polarization-Encrypted Orbital Angular Momentum Multiplexed Metasurface Holography - Zhou, Hongqiang; Sain, Basudeb; Wang, Yongtian; Schlickriede, Christian; Zhao, Ruizhe; Zhang, Xue; Wei, Qunshuo; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (ACS Nano)

Nonlinear imaging with all-dielectric metasurfaces - Schlickriede, Christian; Kruk, Sergey S.; Wang, Lei; Sain, Basudeb; Kivshar, Yuri; Zentgraf, Thomas (Nano Letters)

Second harmonic imaging of plasmonic Pancharatnam-Berry phase metasurfaces coupled to monolayers of WS2 - Spreyer, Florian; Zhao, Ruizhe; Huang, Lingling; Zentgraf, Thomas (Nanophotonics)
The nonlinear processes of frequency conversion such as second harmonic generation (SHG) usually obey certain selection rules, resulting from the preservation of different kinds of physical quantities, e.g. the angular momentum. For the SHG created by a monolayer of transition-metal dichalcogenides (TMDCs) such as WS 2 , the valley-exciton locked selection rule predicts an SHG signal in the cross-polarization state. By combining plasmonic nanostructures with a monolayer of TMDC, a hybrid metasurface is realized, which affects this nonlinear process because of an additional polarization conversion process. Here, we observe that the plasmonic metasurface modifies the light-matter interaction with the TMDC, resulting in an SHG signal that is co-polarized with respect to the incident field, which is usually forbidden for the monolayers of TMDC. We fabricate such hybrid metasurfaces by placing plasmonic nanorods on top of a monolayer WS 2 and study the valley-exciton locked SHG emission from such system for different parameters, such as wavelength and polarization. Furthermore, we show the potential of the hybrid metasurface for tailoring nonlinear processes by adding additional phase information to the SHG signal using the Pancharatnam-Berry phase effect. This allows direct tailoring of the SHG emission to the far-field.

Nonlinear Wavefront Control by Geometric-Phase Dielectric Metasurfaces: Influence of Mode Field and Rotational Symmetry - Liu, Bingyi; Sain, Basudeb; Reineke, Bernhard; Zhao, Ruizhe; Meier, Cedrik; Huang, Lingling; Jiang, Yongyuan; Zentgraf, Thomas (Advanced Optical Materials)
Nonlinear Pancharatnam–Berry phase metasurfaces facilitate the nontrivial phase modulation for frequency conversion processes by leveraging photon‐spin dependent nonlinear geometric‐phases. However, plasmonic metasurfaces show some severe limitation for nonlinear frequency conversion due to the intrinsic high ohmic loss and low damage threshold of plasmonic nanostructures. Here, the nonlinear geometric‐phases associated with the third‐harmonic generation process occurring in all‐dielectric metasurfaces is studied systematically, which are composed of silicon nanofins with different in‐plane rotational symmetries. It is found that the wave coupling among different field components of the resonant fundamental field gives rise to the appearance of different nonlinear geometric‐phases of the generated third‐harmonic signals. The experimental observations of the nonlinear beam steering and nonlinear holography realized in this work by all‐dielectric geometric‐phase metasurfaces are well explained with the developed theory. This work offers a new physical picture to understand the nonlinear optical process occurring at nanoscale dielectric resonators and will help in the design of nonlinear metasurfaces with tailored phase properties.

All-optical switching of a dye-doped liquid crystal plasmonic metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Express)

Nonlinear optics in all-dielectric nanoantennas and metasurfaces: a review - Sain, Basudeb; Meier, Cedrik; Zentgraf, Thomas (Advanced Photonics)
Free from phase-matching constraints, plasmonic metasurfaces have contributed significantly to the control of optical nonlinearity and enhancement of nonlinear generation efficiency by engineering subwavelength meta-atoms. However, high dissipative losses and inevitable thermal heating limit their applicability in nonlinear nanophotonics. All-dielectric metasurfaces, supporting both electric and magnetic Mie-type resonances in their nanostructures, have appeared as a promising alternative to nonlinear plasmonics. High-index dielectric nanostructures, allowing additional magnetic resonances, can induce magnetic nonlinear effects, which, along with electric nonlinearities, increase the nonlinear conversion efficiency. In addition, low dissipative losses and high damage thresholds provide an extra degree of freedom for operating at high pump intensities, resulting in a considerable enhancement of the nonlinear processes. We discuss the current state of the art in the intensely developing area of all-dielectric nonlinear nanostructures and metasurfaces, including the role of Mie modes, Fano resonances, and anapole moments for harmonic generation, wave mixing, and ultrafast optical switching. Furthermore, we review the recent progress in the nonlinear phase and wavefront control using all-dielectric metasurfaces. We discuss techniques to realize all-dielectric metasurfaces for multifunctional applications and generation of second-order nonlinear processes from complementary metal–oxide–semiconductor-compatible materials.

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.

Reconfigurable metasurface hologram by utilizing addressable dynamic pixels - Li, Tianyou; Wei, Qunshuo; Reineke, Bernhard; Walter, Felicitas; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Optics Express)

Silicon metasurfaces for third harmonic geometric phase manipulation and multiplexed holography - Reineke, Bernhard; Sain, Basudeb; Zhao, Ruizhe; Carletti, Luca; Liu, Bingyi; Huang, Lingling; de Angelis, Costantino; Zentgraf, Thomas (Nano Letters)

Metasurface interferometry toward quantum sensors - Georgi, Philip; Massaro, Marcello; Luo, Kai Hong; Sain, Basudeb; Montaut, Nicola; Herrmann, Harald; Weiss, Thomas; Li, Guixin; Silberhorn, Christine; Zentgraf, Thomas (Light: Science & Applications)

Simultaneous Spectral and Spatial Modulation for Color Printing and Holography Using All-dielectric Metasurfaces - Wei, Qunshuo; Sain, Basudeb; Wang, Yongtian; Reineke, Bernhard; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (Nano Letters)

Four‐Wave Mixing Holographic Multiplexing Based on Nonlinear Metasurfaces - Lin, Zemeng; Huang, Lingling; Xu, Zhen Tao; Li, Xiaowei; Zentgraf, Thomas; Wang, Yongtian (Advanced Optical Materials)

Dynamic control of mode modulation and spatial multiplexing using hybrid metasurfaces - Lin, Zemeng; Huang, Lingling; Zhao, Ruizhe; Wei, Qunshuo; Zentgraf, Thomas; Wang, Yongtian; Li, Xiaowei (Optics Express)

Miniaturized Metalens Based Optical Tweezers on Liquid Crystal Droplets for Lab-on-a-Chip Optical Motors - Suwannasopon, Satayu; Meyer, Fabian; Schlickriede, Christian; Chaisakul, Papichaya; T-Thienprasert, Jiraroj; Limtrakul, Jumras; Zentgraf, Thomas; Chattham, Nattaporn (Crystals)
Surfaces covered with layers of ultrathin nanoantenna structures—so called metasurfaces have recently been proven capable of completely controlling phase of light. Metalenses have emerged from the advance in the development of metasurfaces providing a new basis for recasting traditional lenses into thin, planar optical components capable of focusing light. The lens made of arrays of plasmonic gold nanorods were fabricated on a glass substrate by using electron beam lithography. A 1064 nm laser was used to create a high intensity circularly polarized light focal spot through metalens of focal length 800 µm, N.A. = 0.6 fabricated based on Pancharatnam-Berry phase principle. We demonstrated that optical rotation of birefringent nematic liquid crystal droplets trapped in the laser beam was possible through this metalens. The rotation of birefringent droplets convinced that the optical trap possesses strong enough angular momentum of light from radiation of each nanostructure acting like a local half waveplate and introducing an orientation-dependent phase to light. Here, we show the success in creating a miniaturized and robust metalens based optical tweezers system capable of rotating liquid crystals droplets to imitate an optical motor for future lab-on-a-chip applications.

Strong Nonlinear Optical Activity Induced by Lattice Surface Modes on Plasmonic Metasurface - Chen, Shumei; Reineke, Bernhard; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nano Letters)

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Efficient frequency conversion by combined photonic–plasmonic mode coupling - Weber, N.; Hoffmann, S. P.; Albert, M.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Switchable Plasmonic Metasurface Utilizing the Electro-Optic Kerr Effect of a Blue Phase Liquid Crystal - Atorf, Bernhard; Friesen, Simon; Rennerich, Roman; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)

Switchable Plasmonic Metasurface Utilizing the Electro-Optic Kerr Effect of a Blue Phase Liquid Crystal - Atorf, Bernhard; Friesen, Simon; Rennerich, Roman; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)

Volumetric Generation of Optical Vortices with Metasurfaces - Huang, Lingling; Song, Xu; Reineke, Bernhard; Li, Tianyou; Li, Xiaowei; Liu, Juan; Zhang, Shuang; Wang, Yongtian; Zentgraf, Thomas (ACS Photonics)

Directional Emission from Dielectric Leaky-Wave Nanoantennas - Peter, Manuel; Hildebrandt, Andre; Schlickriede, Christian; Gharib, Kimia; Zentgraf, Thomas; Förstner, Jens; Linden, Stefan (Nano Letters)
Keywords: tet_topic_opticalantenna

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Ultrathin Nonlinear Metasurface for Optical Image Encoding - Walter, Felicitas; Li, Guixin; Meier, Cedrik; Zhang, Shuang; Zentgraf, Thomas (Nano Letters)

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Nonlinear optical sub-bandgap excitation of ZnO-based photonic resonators - Bader, Christina A.; Zeuner, Franziska; Bader, Manuel H. W.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

Ag‐nanoparticles in PA-templates - Ezhova, A.; Lindner, Jörg; Muldarisnur, M.; Zentgraf, Thomas; Huber, K.

Blue-green emitting microdisks using low-temperature-grown ZnO on patterned silicon substrates - Ruth, Marcel; Zentgraf, Thomas; Meier, Cedrik (Optics Express)

Dual-polarity plasmonic metalens for visible light - Chen, Xianzhong; Huang, Lingling; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Qiu, Cheng-Wei; Zhang, Shuang; Zentgraf, Thomas (Nature Communications)